Azithromycin and oesophageal motility in chronic respiratory disease: a feasibility study - Dominic L. Sykes; Kayleigh Brindle; Rohan Menon; Simon P. Hart; Jennifer Nielsen; Warren Jackson; John Gallagher; Elisabeth Kirton; Mengru Zhang; Alyn H. Morice; Michael G. Crooks (Therapeutic Advances in Respiratory Disease)
Background: The role of the gut-lung axis in respiratory disease is increasingly recognised. Much emphasis has been placed on gastro-oesophageal reflux disease; however, oesophageal dysmotility may also play a significant role. Azithromycin, a known prokinetic, has been shown to be of major benefit in a number of respiratory diseases, but the relationship between oesophageal function and the lung has not been examined. Objectives: We assessed the feasibility of performing continuous cough monitoring and repeated high-resolution oesophageal manometry (HROM) in patients with chronic respiratory disease. Design: We conducted an open-label, single-arm, feasibility trial. Methods: Azithromycin 250 mg once daily was given to patients with chronic respiratory disease who reported a chronic cough. All participants were monitored continually for at least 1 week prior to and 4 weeks after azithromycin with the Hyfe Cough Tracker. Participants also had HROM performed at two time-points, immediately before and 4 weeks after initiation of azithromycin. Feasibility outcomes pertaining to recruitment, data quality, and acceptability of trial processes were assessed. Exploratory outcome data for metrics of oesophageal function were also analysed. Results: A total of 30 participants (57% female, mean age 65.2 (SD = 11.3)) were recruited over a 10-month period, giving a recruitment rate of three patients per month in a single centre. A total of 87% ( n  = 26) of participants completed all three study visits. All pre-specified data quality outcomes met their ‘green’ traffic light stop-go criteria. HROM demonstrated that the majority (52%) of participants had abnormal oesophageal function, as defined by the Chicago Classification, at baseline. Changes in oesophageal function were not significantly associated with changes in objective or subjective cough measures, except for a weakly negative correlation with the Hull Airway Reflux Questionnaire score. Conclusion: A large-scale trial examining the effect of azithromycin on the relationship between oesophageal function and cough in respiratory disease is feasible and acceptable to patients. Trial registration: This trial was prospectively registered ClinicalTrials.gov ID: NCT05469555.